PENGARUH PROMOSI TERHADAP MINAT BELI DAN KEPUTUSAN PEMBELIAN PADA PENGGUNA EWALLET LINK AJA DI KOTA SURABAYA - Tombo, Yumiati Diana; Aribowo, Handy (Bisnis-Net, 2024)
The purpose of this study is to find out whether product and price affect purchasing decisions for cimory yogurt in the city Surabaya. The method in this study uses quantitative research methods. The population in this study are constumers of cimory yogurt in the city of Surabaya. The sample of this research is 100 respondents. Data collection is using a questionnaire. Whereas for instrument testing using validity and reliability tests and further testing, namely the test and test, as well as the coefficient of determination test. The result show that product quality and price significantly influence purchasing decisions. Respondents agree with the quality and price set by cimory yogurt.